Global Trends in Mortality and Burden of Stroke Attributable to Lead Exposure From 1990 to 2019 - Zhang, Tongchao; Yin, Xiaolin; Zhang, Yuan; Chen, Hui; Man, Jinyu; Li, Yufei; Chen, Jiaqi; Yang, Xiaorong; Lu, Ming (Frontiers in Cardiovascular Medicine, 2022)
Background Lead exposure is an important risk factor for stroke. However, the latest global spatiotemporal patterns of lead exposure-related stroke burden were unclear. In this study, we assessed this topic. Methods The data were obtained from the Global Burden of Disease Study (2019). The estimated annual percentage change (EAPC) was estimated to evaluate the temporal trends of the age-standardized mortality and disability-adjusted life years (DALYs) rates (ASMR and ASDR) of stroke attributable to lead exposure. Results In 2019, the numbers of global stroke deaths and DALYs attributable to lead exposure were 305.27 and 6738.78 thousand, respectively. The corresponding ASMR and ASDR were highest in males, the elderly population, low and middle-income countries, and the intracerebral hemorrhage subtype. From 1990 to 2019, the ASMR and ASDR of global stroke attributable to lead exposure decreased [ASMR: EAPC = −1.34, 95% confidence interval (CI): (−1.57, −1.10); ASDR: EAPC = −1.74, 95% CI: (−1.95, −1.52)], especially in females, the high-income countries, and the subarachnoid hemorrhage subtype. Conclusion This study emphasizes the importance of continued implementation of lead exposure prevention strategies and improved high-efficiency treatment and stroke acute health care, especially in low and middle-income countries.